The phosphodiesterase 8B gene rs4704397 is associated with thyroid function, risk of myocardial infarction and body height. The Tromsø Study - Jorde, Rolf; Schirmer, Henrik; Wilsgaard, Tom; Joakimsen, Ragnar Martin; Mathiesen, Ellisiv B.; Njølstad, Inger; Løchen, Maja-Lisa; Figenschau, Yngve Anton; Svartberg, Johan; Hutchinson, Moira Strand; Kjærgaard, Marie; Jørgensen, Lone; et al. (Thyroid, 2013)
Objective: High serum thyrotropin (TSH) levels predict cardiovascular disease (CVD). Recently several single nucleotide polymorphisms (SNPs) associated with TSH levels have been identified, one of them being the rs4704397 SNP in the phosphodiesterase 8B (PDE8B) gene. If the relation between thyroid function and CVD is causal, one could also expect rs4704397 genotypes to predict CVD and possibly health in general. Methods: DNA was prepared and genotyping performed for rs4704397 in subjects who participated in the fourth survey of the Tromsø Study in 1994–1995 and who were registered with the endpoints myocardial infarction (MI), type 2 diabetes (T2DM), cancer, or death, as well as a randomly selected control group. Similarly, genotyping was performed in subjects who had participated in clinical trials where serum TSH, free T4 (fT4), and free T3 (fT3) were measured. Results: From the Tromsø Study, 8938 subjects without thyroid disease or thyroid medication were successfully genotyped for rs4704397. Among these, 2098 were registered with MI, 1025 with T2DM, 2748 with cancer, and 3592 had died. The minor homozygote genotype (A:A) had a median serum TSH level that was 0.29 mIU/L higher than in the major homozygote genotype (G:G). The A:A genotype had a significantly increased risk of MI as compared to the G:G genotype (1.14 [1.00–1.29], hazard ratio [confidence interval], Cox regression with adjustment for age, sex, and body mass index). No significant associations were seen with the other endpoints or CVD risk factors. Furthermore, subjects with the G:G genotype were significantly taller than subjects with the A:A genotype (mean difference 1.5 cm). In 584 subjects with serum TSH, fT4, and fT3 measurements, the subjects with the A:A genotype had significantly higher serum TSH and nonsignificantly lower serum fT3 (mean difference 0.15 pmol/L) levels than subjects with the G:G genotype. Conclusion: rs4704397 is associated with thyroid function, risk of MI, and body height. However, confirmation in other cohorts is ...